An exploration of the experiences of professionals supporting patients approaching the end of life in medicines management at home. A qualitative study - Wilson, Eleanor (BMC Palliat Care, 2020)
BACKGROUND: The management of medicines towards the end of life can place increasing burdens and responsibilities on patients and families. This has received little attention yet it can be a source of great difficulty and distress patients and families. Dose administration aids can be useful for some patients but there is no evidence for their wide spread use or the implications for their use as patients become increasing unwell. The study aimed to explore how healthcare professionals describe the support they provide for patients to manage medications at home at end of life. METHODS: Qualitative interview study with thematic analysis. Participants were a purposive sample of 40 community healthcare professionals (including GPs, pharmacists, and specialist palliative care and community nurses) from across two English counties. RESULTS: Healthcare professionals reported a variety of ways in which they tried to support patients to take medications as prescribed. While the paper presents some solutions and strategies reported by professional respondents it was clear from both professional and patient/family caregiver accounts in the wider study that rather few professionals provided this kind of support. Standard solutions offered included: rationalising the number of medications; providing different formulations; explaining what medications were for and how best to take them. Dose administration aids were also regularly provided, and while useful for some, they posed a number of practical difficulties for palliative care. More challenging circumstances such as substance misuse and memory loss required more innovative strategies such as supporting ways to record medication taking; balancing restricted access to controlled drugs and appropriate pain management and supporting patient choice in medication use. CONCLUSIONS: The burdens and responsibilities of managing medicines at home for patients approaching the end of life has not been widely recognised or understood. This paper considers some of the strategies reported by professionals in the study, and points to the great potential for a more widely proactive stance in supporting patients and family carers to understand and take their medicines effectively. By adopting tailored, and sometimes, ‘outside the box’ thinking professionals can identify immediate, simple solutions to the problems patients and families experience with managing medicines.